Ancient Rhamnaceae flowers impute an origin for flowering plants exceeding 250-million-years ago - Tianhua He; Byron B. Lamont (iScience, 2022)
Summary: Setting the molecular clock to newly described 100-million-year-old flowering shoots of Phylica in Burmese amber enabled us to recalibrate the phylogenetic history of Rhamnaceae. We traced its origin to ∼260 million years ago (Ma) that can explain its migration within and beyond Gondwana since that time and implies an origin for flowering plants that stretches well beyond 290 Ma. Ancestral trait assignments also revealed that hard-seededness, fire-proneness, and to a lesser extent, heat-released seed dormancy, have a similarly long history in this clade.